The Role of Social Media in Digital Marketing Communication For Healthy Behaviour - Erlina Puspitaloka Mahadewi; Astrid Chrisafi; Ritta Setiati; Dwi Nurmawaty; Elistia Elistia; Dina Sudarmika; Sam Salomon (International Journal of Health and Pharmaceutical (IJHP), 2026)
The aim of this research is to analyze the communication challenges in the Social Media in Digital Marketing Communication (DMC) era, and understanding generation millenial  for healthy digital behaviour. This research is a literature review. Data collection using documentation from Google Scholar. Data analysis using Systematic Literature Review (SLR). Communication challenges in the current digital era, especially in interacting with generation Millenial, is a very wide expansion of the communication field through various digital platforms, such as social media, instant messaging, and online content. Generation Millenial (GM) has unique characteristics that influence the way they communicate, such as a preference for short messages, images and videos that are effective in conveying messages. Understanding and adapting your communication style to them is important for building strong and effective relationships. In addition, it must be acknowledged that generation millenial has a high level of technological awareness, which can raise privacy and security issues that must be managed wisely in an effort to establish successful communication with this generation.